Galectin-3 binding protein plasma levels are associated with long-term mortality in coronary artery disease independent of plaque morphology - Gleißner, Christian A.; Erbel, Christian; Linden, Fabian; Domschke, Gabriele; Akhavanpoor, Mohammadreza; Dösch, Andreas; Buß, Sebastian Johannes; Giannitsis, Evangelos; Katus, Hugo; Korosoglou, Grigorios (Atherosclerosis, 2016)
Background and aims Galectin-3 binding protein (Gal-3BP) is a secreted protein associated with inflammation and carotid atherosclerosis. We hypothesized that high Gal-3BP levels may indicate unfavorable plaque morphology and outcome in coronary artery disease (CAD). Methods Gal-3BP plasma levels were measured by ELISA in 233 patients (63 ± 10 years, 50.2% male) undergoing computed coronary angiography tomography (CCTA). Results In 149 patients, CCTA confirmed CAD (stenosis grade >20%). Mean Gal-3BP plasma levels were 5.9 ± 2.7 μg/mL and did not differ between patients with or without CAD. Over a follow-up time of up to 4.4 years (median 2.5 years), there were 17 cases of revascularization, five cases of myocardial infarction, and five deaths (four non-cardiac, one fatal myocardial infarction). Kaplan-Meier analysis revealed that high Gal-3BP levels were significantly associated with long-term mortality (p < 0.001). Cox proportional hazards regression analysis showed that this association was independent of cardiovascular risk factors (HR 1.238, 95%-CI 1.012-1.514, p = 0.038). After adjustment for troponin T and C-reactive protein (hs-CRP) levels, significance was lost (p = 0.123). Further analysis revealed that Gal-3BP levels were significantly related to body mass index and hs-CRP levels indicating an association with metabolic and inflammatory distress. There was no correlation between Gal-3BP and calcium score, plaque volume, or vascular remodeling. Conclusions While high Gal-3BP plasma levels are associated with long-term mortality, we could not confirm it as a marker of cardiac mortality or unstable plaque morphology.
Gesehen am 20.11.2018